THE ROLE OF CIVIC EDUCATION IN ENHANCING COMMUNITY WELFARE THROUGH SOCIAL PARTICIPATION - Hanif, Muh.; Suherlan; Az Zaakiyyah, Hizbul Khootimah (Technopreneurship and Educational Development Review (TENDER), 2024)
Civic Education (PKn) plays a significant role in enhancing community welfare through active and meaningful social participation. This study employs a literature review method with a qualitative approach and descriptive analysis, using data from 19 selected scholarly articles from 2010-2024 sourced from Google Scholar. The findings show that PKn is capable of building the public’s understanding of their rights and duties as citizens, instilling values of solidarity, tolerance, and mutual cooperation, and encouraging active participation in decision-making and the management of local resources. Case studies such as community-based waste management in Sukunan Village and the development of a tourist village in Pentingsari emphasize that effective PKn programs can improve the economic and social welfare of communities. However, PKn implementation faces challenges such as limited resources, lack of policy support, and the need for adaptation in the digital era. This research recommends strengthening policies, integrating technology, adopting contextual approaches, fostering multi-party collaborations, and conducting monitoring and evaluation to optimize the role of PKn in creating sustainable community welfare.